Dividend Policy and Share Price Volatility of Listed Micro Finance Companies in Nepal - Hem Bahadur Thapa (Journal of Balkumari College, 2025)
The major purpose of this study is to examine the impact of dividend policy on share price volatility of listed micro finance companies in Nepal. The study follows quantitative approach and descriptive research design. Multiple regression analysis is used to explore the causal relation between share price volatility and both dividend yield and dividend payout ratio. The study reveals a positive relationship of dividend yield, dividend payout, earning volatility, debt, growth of assets with share price volatility which shows higher the dividend yield, dividend payout, earning volatility, debt, growth of assets, higher would be the share price volatility. However, there is negative relationship between size and share price volatility showing higher the size of the company, lower would be the share price volatility. Since both management and investors are concerned about the volatility of stock price, this study provides a light on the pathway for discovering what moves stock price as well as important factors to be considered by investors before making investment decision.